Quality of Life, Depression and Involvement in Physical Activity of Parents with Disabled Children in Greece (Calidad de vida, depresión y participación en actividad física de los padres de niños discapacitados en Grecia) - Skordilis, Emmanouil K (Retos, 2015)
The study examined the quality of life (QoL) of parents with disabled children in Greece. Further, the relationship between QoL with depressive symptoms and involvement in physical activity were reported as well. The total sample constituted from 73 parents (Mean age = 42.87 years, SD = 7.58), classified to 42 parents of children with disabilities and 31 parents of children without disabilities (control group). The participants responded to the Beck Depression Inventory II (BDI-II) (Beck, Steer & Garbin, 1996), the QoL SF36v2 scale (Ware et al., 2007), and the Self Administered Physical Activity Checklist (SAPAC) (Sallis, Strikmiller, Harsha, & Feldman, 1996). The multivariate (lambda = .99, F = .35, p = .70, eta2 = .01) and univariate comparisons between the two parental groups did not reveal significant differences in the physical (PCS) and mental components (MCS) of the SF36v2. The QoL was significantly related to the depressive symptoms, while the involvement in physical activity was not related to QoL. On the other hand, parents of children with disabilities had less sedentary behaviors compared to the control group. The overall findings are discussed in line with relevant studies examining the QoL of families with disabled children. Keywords. Quality of Life, depression, physical activity, parents, disability. Resumen. Este estudio examinó la calidad de vida (QoL) de los padres de niños discapacitados en Grecia. Además, se reporta la relación entre la calidad de vida y los síntomas depresivos y de la participación en actividades físicas. El total de la muestra estuvo constituida por 73 padres (edad promedio = 42.87 años, DE = 7.58), clasificadas en 42 padres de niños con discapacidad y 31 padres de niños sin discapacidad (grupo control). Los participantes respondieron el Inventario de Depresión de Beck II (BDI-II) (Beck, Steer & Garbin, 1996), la escala QoL SF-36 v2 (Ware et al., 2007), y el Self Administered Physical Activity Checklist (SAPAC) (Sallis, Strikmiller, Harsha, & Feldman, 1996). Las comparaciones multivariadas (lambda = .99, F = .35, p = .70, eta2 = .01) y univariadas entre los dos grupos de padres no mostró diferencias significativas en los componentes físicos (PCS) y mentales (MCS) de la escala SF-36. La QoL se relacionó significativamente con síntomas depresivos, mientras que la participación en actividades físicas no estuvo relacionada con la QoL. Por otra parte, los padres de los niños con discapacidad tuvieron menos comportamientos sedentarios comparados con los padres del grupo control. Los resultados generales se discuten en línea con los estudios pertinentes que examinan la calidad de vida de las familias con niños discapacitados. Palabras claves. Calidad de vida, depresión, actividad Física, padres, discapacidad